PP.37.24: MYOCARDIAL OXYGEN CONSUMPTION IN PATIENTS WITH SLEEP APNEA-HYPOPNEA SYNDROME. (June 2015) - Davidovic, G.; Vuckovic-Filipovic, J.; Milanov, S.; Cekerevac, I.; Iric-Cupic, V.; Miloradovic, V.; Petrovic, M.; Simovic, S.
Abstract : Objective: Sleep apnoea-hypopnea syndrome is defined as the cessation of breathing during sleepwhich lasts for at least 10 seconds, on 5 or more occasions per hour. Apnoeic episodes result in hypoxia and hypercapnia which lead to higher sympathetic activation. Blood pressure elevation results in increased myocardial oxygen demand, with simultaneous reduction in oxygen supply due to hypoxia. Double product, or rate pressure product is an indirect measure of myocardial oxygen consumption. Aim was to indirectly determine the effect of hypoxia on myocardial oxygen consumption estimated via double product. Design and method: Research included 100 patients who underwent polysomnograpic examination in UCC Kragujevac. According to apnea-hypopnea index (AHI) all patients were divided into 4 equal groups, 25 patients in each group (AHI <5; 5–15; 15–30 and >30). ABPM was performed in all patients and myocardial oxygen consumption was estimated indirectlly. RPP was calculated for 24 h period automatically through formula integrated into ABPM: RPP = HR(bpm)*SBP(mmHg), with defining RPP >10.000 bpm/mmHg as threshold for low/high oxygen consumption. All data were statistically analyzed in the SPSS for Windows. Results: Among 100 patients, 69 (69%) were male and 31 (31%) were female, with the mean age of 55.05 ± 11.16 years. Oxygen deasturation index was significantlly higher in group with sleep apnea, with mean values of 24.87 ± 17.91 (t-test; p = 0.000). Mean SaO2 was 92.02 ± 4.06. Systolic blood pressure on ABPM was 130.67 ± 18.28 mmHg, and heart rate had a mean value of 74.80 ± 10.90 bpm. Rate pressure product (double product) was lower than 10.000 bpm/mmHg in 66 patients (66%; x2-test = 10.24; p = 0.001) having the mean value of 9363.41 ± 1974.63 bpm/mmHg. There was a significant positive correlation of RPP to AHI (r = 0.208; p = 0.038). Conclusions: Sleep apnoea induced significant decrease in oxygen saturation, which diminished myocardial oxygen supply and thus, the myocardial oxygen consumption. Long-term hypoxia and insufficient oxygen supply to myocardium represent a significant factor for future cardiovascular events, especially ischaemia, so special attention and therapy consideration is needed about this issue.